2018
DOI: 10.3390/s18010261
|View full text |Cite
|
Sign up to set email alerts
|

Neuromorphic Vibrotactile Stimulation of Fingertips for Encoding Object Stiffness in Telepresence Sensory Substitution and Augmentation Applications

Abstract: We present a tactile telepresence system for real-time transmission of information about object stiffness to the human fingertips. Experimental tests were performed across two laboratories (Italy and Ireland). In the Italian laboratory, a mechatronic sensing platform indented different rubber samples. Information about rubber stiffness was converted into on-off events using a neuronal spiking model and sent to a vibrotactile glove in the Irish laboratory. Participants discriminated the variation of the stiffne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…We showed that the presented tactile telepresence system enabled the correct discrimination of the inclusions throughout the polymeric matrix, especially for the stiffer ones, in both ILS and NILS telepresence conditions. This work enriches the findings of our previous works [43,[48][49][50], confirming that the adoption of spike-like stimulation, emulating the firing activity of skin mechanoreceptors, offers a usable language of feedback that can be delivered directly on the skin surface, to provide perceptual The CDF fitting function, introduced in Section 2 and reported in Equation (1), represents the probability of a correct response at a stiffness x, where a denotes the perceptual threshold, and b > 0 a scale parameter that affects the curve steepness. With respect to our previous study [43], the equation has been updated in order to account for an identification task rather than for a two-alternatives forced choice task.…”
Section: Discussionsupporting
confidence: 89%
“…We showed that the presented tactile telepresence system enabled the correct discrimination of the inclusions throughout the polymeric matrix, especially for the stiffer ones, in both ILS and NILS telepresence conditions. This work enriches the findings of our previous works [43,[48][49][50], confirming that the adoption of spike-like stimulation, emulating the firing activity of skin mechanoreceptors, offers a usable language of feedback that can be delivered directly on the skin surface, to provide perceptual The CDF fitting function, introduced in Section 2 and reported in Equation (1), represents the probability of a correct response at a stiffness x, where a denotes the perceptual threshold, and b > 0 a scale parameter that affects the curve steepness. With respect to our previous study [43], the equation has been updated in order to account for an identification task rather than for a two-alternatives forced choice task.…”
Section: Discussionsupporting
confidence: 89%
“…The LDSI filter is compared to a commonly used jAER software filter, providing improved results, especially in complex situations with fast moving objects in the scene. The LDSI filter can be used in any scenario where the input consists on a matrix sensor generating events, not only image sensors but also other event sensors, such as auditory [3], distance measurement or magnetic compass [34], olfactory systems [4,5], and tactile [37] sensors.…”
Section: Discussionmentioning
confidence: 99%
“…The neuromorphic activation of the transducer was achieved by setting the input to the neuron proportional to the magnitude of the normal force measured by the remote subsystem. Further details about the neural model and a definition of its parameters can be found in our previous works [43,48]. Initial calibrations were also performed to counterbalance the effect of saturation of the neural model [48].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work [43], we developed a mechatronic platform interfaced with a vibro-tactile glove for tactile augmentation in telepresence under passive exploration of remote stimuli. The results demonstrated the efficiency of the system in presenting mechanical information about test objects.…”
Section: Introductionmentioning
confidence: 99%